BATASAN PENGGUNAAN HAK UNTUK DILUPAKAN BERDASARKAN PASAL 26 UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK TERHADAP MANTAN NARAPIDANA DI INDONESIA - Dhea Natalie Simarmata; Mukhlis R; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Internet and information technology at this time is very important for the fulfillment ofhuman needs. Because the rapid development of information technology has created dynamics inthe midst of society, a management and regulation is needed that specifically addresses problemsin the field of Information and Electronic Transactions (ITE). However, in several respects, theITE Law still has weaknesses. One of the weaknesses that is still being debated today is theregulation regarding the right to be forgotten as contained in Article 26 paragraphs (3) and (4).From that article, there is no clear element of limitation to be able to carry out the execution ofthe right to be forgotten, especially for ex-convicts in Indonesia. In this case the limitation ofrights in administrative law must pay attention to the norms in criminal law which the authorwill further describe. The right to be forgotten should accommodate the norms contained in thepurpose of punishment. The controversy over the use of this right by ex-convicts will potentiallybe used to obscure past crimes.This type of research can be classified in the type of normative legal research, whichreveals laws and regulations related to legal theories that are the object of research. Theapproach taken uses a qualitative analysis approach by searching for good data in books,journals and other scientific works related to this research. The data sources used are primaryand secondary legal materials.The conclusions that can be obtained from the research results are First, the regulationregarding the right to be forgotten for ex-convicts in Indonesia is not in accordance with thepurpose of punishment. The status of ex-convicts who are still attached with a greater chance ofrepeating crimes makes limiting the rights of ex-convicts something that has legal logic to tacklecrime, especially repeated crimes in the Theory of Criminal Policy. Second, the ideal concept oflimiting the right to be forgotten for ex-convicts in Indonesia should refer to the General DataProtection (GDPR) which applies throughout the European Union. This right should not begiven to ex-convicts and must be further regulated regarding additional punishments related tothe revocation of the right to be forgotten by ex-convicts.Keywords: Right To Be Forgotten- ITE-Former Convicts-Limitation of Rights.